Time-efficient and beneficial strategy: low-volume high-intensity interval training for cardiometabolic health and body composition outcomes in children and adolescents with overweight or obesity—a systematic review and meta-analysis - Ye, Chenxin; Fu, Honghao; Zhou, Xiao; Zhang, Zhi (Frontiers in Physiology, 2026)
ObjectivesThis meta-analysis aimed to synthesize evidence on the effects of low-volume high-intensity interval training (LV-HIIT) on body composition and cardiometabolic health in overweight and obese children and adolescents. Specifically, we sought to: (1) quantify the effects of LV-HIIT versus non-exercise controls; (2) directly compare LV-HIIT with moderate-intensity continuous training (MICT); (3) identify participant- and program-level moderators prespecified subgroup and meta-regression analyses, to inform time-efficient pediatric exercise prescriptions.MethodsSix databases (PubMed, EMBASE, Cochrane Library, Web of Science, CNKI, and EBSCO) were systematically searched. Randomized controlled trials comparing LV-HIIT with either MICT or inactive controls in participants aged 7–16 years with overweight or obesity were included. Using random-effects models to calculate standardized mean differences with 95% confidence intervals Subgroup and meta-regression analyses were conducted to identify potential moderators.ResultsTwelve trials involving 609 participants were included. Compared with non-exercise controls, LV-HIIT reduced BMI (SMD = −1.15, 95% CI [−1.68, −0.61]), body fat percentage (SMD = −0.84, 95% CI [−1.09, −0.59]), waist circumference (SMD = −0.62, 95% CI [−0.93, −0.32]), systolic blood pressure (SMD = −0.80, 95% CI [−1.11, −0.49]), diastolic blood pressure (SMD = −0.47, 95% CI [−0.77, −0.17]), while increasing VO2max (SMD = 2.10, 95% CI [1.32, 2.87]). Compared with MICT, LV-HIIT showed greater improvements in BMI (SMD = −0.27, 95% CI [−0.49, −0.04]), systolic blood pressure (SMD = −0.25, 95% CI [−0.55, −0.05]), and VO2max (SMD = 0.76, 95% CI [0.39, 1.13]), while showing comparable effectiveness in reducing body fat percentage (SMD = −0.06, 95% CI [−0.35, 0.22]) and waist circumference (SMD = −0.37, 95% CI [−0.75, 0.01]). Subgroup analyses revealed greater BMI reductions with LV-HIIT among participants who were overweight at baseline and among males. Meta-regression with baseline adiposity as a continuous moderator indicated participants with lower baseline BMI may experience greater BMI reductions after LV-HIIT.ConclusionLV-HIIT significantly improves body composition, cardiometabolic health, and cardiorespiratory fitness in overweight and obese children and adolescents, offering comparable or superior benefits to traditional MICT in approximately half the time.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420250655540.